Sports in the French Association of the Paralyzed: difficulties in creating and maintaining a consensual policy - Clément Gazza (Karolinum Press, 2017)
The aim of this research is to provide a better understanding of the effects of a trying to create sports policy within an organization that is not familiar with this subject. Participant observation, plus 46 interviews, revealed the difficulties in setting up a real policy within the French Association of the Paralyzed. Because of heterogeneous points of view, the development of these activities remains more like roughly assembled guidelines rather than a real sports policy. Nevertheless, we should be able to obtain a consensus in creating awareness, in training and bringing the support people to use physical activities in their caring practices.